Study on Varying Characteristics of Temperature Field and Moisture Field of Shallow Loess in the Freeze-Thaw Period - Hui Zhang; Bin Zhi; Enlong Liu; Tiehang Wang (Advances in Materials Science and Engineering)
The moisture and the temperature variation of shallow loess during the freeze-thaw process have tremendous influences on the freeze-thaw disease and agricultural development. The present paper, based on the field test of the temperature and water content of the shallow loess in the seasonal frozen region, probes into the variation of the temperature and moisture fields of shallow loess in the freeze-thaw period. Field test shows that the daily variation of surface temperature reaches the maximum with the peak temperature appearing around 14:00, and the time when the peak temperature appears gradually postpones as the depth increases. Moreover, the daily variation of soil temperature decreases with the increase of temperature, and the variation can be ignored given the depth of more than 30 cm. In addition, there is an obvious variation of moisture content in shallow soil under the action of freeze-thaw cycles. In this regard, the coupled calculation model is proposed in this paper to simulate the dynamic variation of temperature and moisture in shallow soil in Bin County located in Western China under natural conditions, compare the calculation value with the measurement value, and further verify the rationality of the numerical calculation method and parameter selection. Furthermore, the variation law of the maximum frozen depth with the air temperature is obtained through the simulation of extreme cold climate conditions.